A development of temperature control simulation on YEWPACK MARK II system / Hamadi Tani and Mustapa Kamal Mohd Kassim - Tani, Hamadi; Mohd Kassim, Mustapa Kamal (1989)
The advent of low-cost and yet powerful process computer systems has made it more convenient now to implement advanced process control to improve control performance and hence plant profitabi1ity.Advanced process control techniques are much more sophisticated than the simple PID controllers and thus, it is essential that a correct process simulation 'based on the knowledge of process dynamics be developed for control operations and also training purposes. This project shows one of the application of the YENPACK MARK II process computer system through a simulation of a batch process for temperature control in a reactor. A graphical simulation for the process and the reactor has been developed, thus the operation could be carried out from a simple and understandable operator terminal.